Sexual Violence Survivors’ Experiences with the Police and Willingness to Report Future Victimization - Lorenz, Katherine (Women & criminal justice, 2024)
Sexual assault is a highly underreported crime with many survivors feeling dissatisfied regarding their contact with the police. While procedural justice can improve police interactions, it has received little consideration concerning its potential to improve the experiences of sexual assault survivors. We explore the relationship between interactions with detectives during an investigation and survivors’ willingness to report to the police in the future through a procedural justice framework using a U.S. community sample of sexual assault survivors. Quantitative data show willingness to report future crimes when survivors perceived adherence to procedural justice in their interactions with the detective(s). Qualitative data indicated that future reporting was influenced by the treatment survivors received by the police as well as other factors (e.g., altruistic motives, ability to self-advocate). We discuss implications for policing practices based on our findings to improve access to justice for survivors that minimizes risk of secondary victimization.